The intimate talk between plants and microorganisms at the leaf surface. (9th October 2017) - Aragón, Wendy; Reina-Pinto, José Juan; Serrano, Mario
Abstract : The plant cuticle plays a key role in regulating the intimate interactions between plants and the pathogenic and non-pathogenic bacteria and fungi that inhabit the phyllosphere. Abstract: The plant epidermis or cuticle is constantly exposed to external and internal environmental factors, including an enriched and diverse community of bacteria, yeast, fungi, viruses, and mites. It is not only where the plant has its first physical barrier, but also where organisms can be recognized and potentially where the plant defense responses can be triggered. The plant cuticle is a polymeric composite formed by an array of structurally and chemically heterogeneous compounds, including cutin and wax. A few studies have shown that cuticular components are essential and important drivers of the structure and size of the bacterial community. On the other hand, cuticular components are also important for both pathogens and plants, to initiate the pre-invasion and infection process and to activate the innate immune response, respectively. In this review, we explore current knowledge on the role of the cuticle during the intimate interactions between plants and microorganisms, in particular pathogenic and non-pathogenic bacteria and fungi. Finally, we propose new perspectives on the potential use of this information for agriculture.